Vitamin E beyond Its Antioxidant Label - Ungurianu, Anca (Antioxidants (Basel), 2021)
Vitamin E, comprising tocopherols and tocotrienols, is mainly known as an antioxidant. The aim of this review is to summarize the molecular mechanisms and signaling pathways linked to inflammation and malignancy modulated by its vitamers. Preclinical reports highlighted a myriad of cellular effects like modulating the synthesis of pro-inflammatory molecules and oxidative stress response, inhibiting the NF-κB pathway, regulating cell cycle, and apoptosis. Furthermore, animal-based models have shown that these molecules affect the activity of various enzymes and signaling pathways, such as MAPK, PI3K/Akt/mTOR, JAK/STAT, and NF-κB, acting as the underlying mechanisms of their reported anti-inflammatory, neuroprotective, and anti-cancer effects. In clinical settings, not all of these were proven, with reports varying considerably. Nonetheless, vitamin E was shown to improve redox and inflammatory status in healthy, diabetic, and metabolic syndrome subjects. The anti-cancer effects were inconsistent, with both pro- and anti-malignant being reported. Regarding its neuroprotective properties, several studies have shown protective effects suggesting vitamin E as a potential prevention and therapeutic (as adjuvant) tool. However, source and dosage greatly influence the observed effects, with bioavailability seemingly a key factor in obtaining the preferred outcome. We conclude that this group of molecules presents exciting potential for the prevention and treatment of diseases with an inflammatory, redox, or malignant component.